1999
DOI: 10.1152/jappl.1999.86.5.1552
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bilateral vestibular lesions on orthostatic tolerance in awake cats

Abstract: Previous experiments in anesthetized or decerebrate cats showed that the vestibular system participates in adjusting blood pressure during postural changes. The present experiments tested the hypothesis that removal of vestibular inputs in awake cats would affect orthostatic tolerance. Before the lesion, blood pressure typically remained within 10 mmHg of baseline values during nose-up-pitch body rotations of up to 60 degrees in amplitude. In contrast, bilateral peripheral vestibular lesions altered the patter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
97
3

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 111 publications
(112 citation statements)
references
References 18 publications
(19 reference statements)
12
97
3
Order By: Relevance
“…In particular, only 3 neurons with graviceptive responses that were best activated by pitch rotations were detected in this study. This observation is curious considering that the CVN participate in correcting disturbances in blood pressure and breathing elicited by sustained head-up pitch of the body (Uchino et al 1970;Yates et al 1993;Woodring et al 1997;Kerman and Yates 1998;Jian et al 1999;Cotter et al 2001;Cotter et al 2004;Wilson et al 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, only 3 neurons with graviceptive responses that were best activated by pitch rotations were detected in this study. This observation is curious considering that the CVN participate in correcting disturbances in blood pressure and breathing elicited by sustained head-up pitch of the body (Uchino et al 1970;Yates et al 1993;Woodring et al 1997;Kerman and Yates 1998;Jian et al 1999;Cotter et al 2001;Cotter et al 2004;Wilson et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…It is thus unclear whether these alterations in vestibular nucleus neuronal activity elicited by postural changes in animals lacking labyrinthine inputs have functional significance. Previous studies showed that lesions of the CVN result in long-lasting or permanent impairments in adjusting blood pressure during postural alterations (Mori et al 2005), whereas the effects of a bilateral vestibular neurectomy on cardiovascular control dissipate within a week (Jian et al 1999), suggesting that integrity of the CVN is essential for adequate autonomic responses during movement. However, the present data do not address whether modulation of the activity of CVN neurons during changes in body position is essential for these responses to occur.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BPD infants presented with greater intersubject variability in BP responses to head-up tilt than controls. Vestibular dysfunction is expected to result in greater variability in BP during postural changes (10). Therefore, the increased variability in the present study likely results from the dysfunction of vestibulo-mediated cardiovascular control observed, instead of altered baroreflex function.…”
Section: Discussionmentioning
confidence: 71%
“…The dysfunction results in greater variability in BP control during postural changes (10). Similarly, increased BP variability has been observed in tilt tests performed in infants who have suffered from apparent life-threatening events (ALTEs) (11,12), further supporting the idea of vestibular dysfunction in SIDS.…”
mentioning
confidence: 77%